Representation of Feminism in the Novel Jatisaba - Santi Gusfitasari; Mindani Mindani; Bustomi Bustomi (Yayasan Karinosseff Muda Indonesia, 2022)
Background of the problem raised in this research was how the form of feminism and the role of feminism in the novel Jatisaba by Ramadya Akmal. The purpose of this study was to find out how the form of feminism and the role of feminism in the novel Jatisaba by Ramadya Akmal. The method used in this research was descriptive qualitative method, and the approach used in this research was the literary criticism approach of feminism. The data source was the novel Jatisaba by Rmadya Akmal. The data collected in the form of words and quotes. Data collection techniques was in the form of library techniques. The data validity technique was focused on trust testing which consists of two activities, namely increasing persistence and using reference materials. The data analysis technique used the Miles and Huberman analysis model. The results of this study were that the form of feminism and the role of feminism found in the novel Jatiaba by Ramadya Akmal, which was in the form of feminism in the novel, told about a village called Jatisaba, the majority of the population of this village are Indonesian Labor, many Indonesian labor brokers enter the village, one of which was Mae. Many villagers had been victims of violence during their time as migrant workers, both physical and non-physical. The researcher could conclude that women in Jatisaba village experience a lot of physical and non-physical violence. Mae and other Indonesian labor brokers only took advantage of the existing conditions in the village.